History and Eschtology in the Lazarus Narrative John 11.1–44 - Martin, James P. (Scottish journal of theology, 1964)
Two questions are usually asked concerning the historical J. value of the Lazarus narrative. One question is whether or not Lazarus rose from the dead. This will be answered by arguments concerning the possibility of miracles, but John is not concerned to indulge in such arguments. The other question is about the place of this event in the course of Jesus' ministry. If the synoptic tradition is taken as the norm, the historical value of the Lazarus story seems threatened. We appear to be forced to choose between the cleansing of the Temple (Mark 11.8) and the raising of Lazarus (John 11.47–53) as the direct cause of the final plot to kill Jesus. There is, however, no certainty that one event alone caused the final decision against Jesus; both Mark and John are aware of other attempts and plots (Mark 3.6, John 7.32).